PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS IV SDN 14 GADUT KABUPATEN AGAM - Yumeriza, Intan; Adrias, Adrias; Rahmi, Gita; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading comprehension skills of fourth-grade students at SDN 14 Gadut, Agam Regency. Key issues identified included students' difficulties in grasping the meaning of narrative texts, an inability to independently identify and locate main ideas within paragraphs, low learning motivation, and challenges regarding collaboration in completing group tasks on time. Furthermore, the teaching modules used by the teacher did not specifically adopt a particular model, and learning activities remained dominated by a teacher-centered approach. Initial assessments revealed that 56.25% of students failed to meet the established Learning Objective Mastery Criteria (KKTP). This study aims to provide an in-depth description of the improvement of fourth grade students' reading comprehension through the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model. The study employs a Classroom Action Research (CAR) methodology, designed collaboratively with the classroom teacher. It was conducted over two cycles, with each cycle systematically comprising the stages of planning, action implementation, observation, and reflection. The research subjects were all 16 fourth grade students at SDN 14 Gadut, Agam Regency comprising 11 boys and 5 girls during the 2025/2026 academic year. Data collection was conducted comprehensively using observation and testing techniques. The research instruments utilized included a teaching module assessment sheet based on the Deep Learning approach, teacher and student activity observation sheets, and a learning outcome evaluation sheet covering attitudes, knowledge, and reading performance skills, as well as assessments of student presentations and discussions.